STUDI FENOMENOLOGIS DINAMIKA PSIKOLOGIS SANTRI PEMBELAJAR - Saifullah Saifullah; Abd Mughni (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2016)
This study was qualitative-phenomenological approach aimed to identifying and understanding more deeply about the self-regulated learning of islamic boarding school students. The subjects of this study consist of 3 islamic students were lived in boarding scool. The results indicated that the three subjects conducted self-regulation in learning through regulating the metacognition, motivation, behavior, help seeking in order toÂ achieve certain learning objectives. Self-regulated learning performed by the subjects was influenced by specific precipitating situations and the social support that given to them.